Flavonoids from the Genus Astragalus: Phytochemistry and Biological Activity - Bratkov, Viktor M.; Shkondrov, Aleksandar M.; Zdraveva, Petranka K.; Krasteva, Ilina N. (Pharmacognosy Reviews)
Flavonoids, the most common plant polyphenols are widely distributed in every species and possess a broad range of pharmacological activities. The genus Astragalus is the largest in the Fabaceae family with more than 2,500 species spread. They are known to contain different metabolites such as flavonoids, saponins, and polysaccharides. Plants from the genus have been used in the traditional medicine of many countries for centuries. This paper is focused on the large group of flavonoid compounds. Details on structure as well as information about the pharmacological properties of flavonoids, isolated from Astragalus species have been discussed. This review is based on publications until the first half of 2014 and includes also the results from our phytochemical investigations of the genus.
Keywords: Astragalus; biological activity; flavonoids; phytochemistry